Repetition is a characteristic and aesthetic style in Mansoor Alhilou's poetry - Alhilo, Wasan (Al-Adab Journal, 2023)
We must say that the poems of the poet Mansoor Mahmood Alhilou has not been studied before and we are the first who study his poems rhetorically and his way of writing (repetition) is something distinguishable and colors his poems. We are standing on the consistency with the structure of the poems and then we find that repetition has a powerful effect on the poem and rises it.